POST-ISLAMISM AND ART CINEMA IN INDONESIA: QUESTIONING THE FREEDOM AFTER REVOLUTION IN MUSLIM MAJORITY COUNTRIES - Bunk, Putri (PEOPLE: International Journal of Social Sciences, 2019)
Post-Islamism is an ideology that fights against Islamic political upsurge, and if applied in a Muslim country or a majority Muslim country, it would be free to exercise true democracy that celebrates freedom from its previous extremist regime. The lack of freedom hinges upon creativity and success in the art world, including cinema, the most powerful media that reflects on the progression of humanity. Malaysian Cinema has received very little international recognition despite its early establishment in the 1930s. Film narratives that deal with human struggles revolving around inequalities, social and racial imbalance, poverty and religious reinterpretations, are often the basis for international acclaim. These types of narratives that deal with social realism are largely absent from Malaysian cinema. This scenario reflects largely on the competitive-authoritarian regime that the country went through for the past 61 years, up until recently, when she finally managed to topple the previous autocratic government. To prove that what is happening in Malaysia is a lack of freedom, and because Malaysia just recently beginning to experience its reform transition, this paper is going to reflect on Indonesia- a country that shares a lot of similarities with Malaysia, predominantly its geography, language, religion and its multi-ethnicity background-, which has already received their reform from 1998, to investigate how a society during its height of reform experience freedom especially in its cinema industry. This paper draws a connection between the sudden success of the Indonesian Cinema has a direct connection with the elements of Post-Islamism that emerged during the post-New Order era. Using Asef Bayat’s sociologist definition of Post-Islamism, this paper will aim to analyze the success of the Indonesian Cinema between 1998 to 2008. The paper hypothesizes that its revolutionary success is linked to the freedom of expression under Post-Islamism concept which was possible within the Islamic periphery for a 10-year-period until the introduction of the Anti-Pornography Bill. The controversial bill was signed into effect in 2008 and has since been used to curb freedom of expression and once again stifle narrative creativity in local films. This scenario reflects on the similar state of a control the Malaysian cinema undergo. The paper concludes that by adapting the Post-Islamism for the countries’ nation building using cinema as one of the culture change agents, they could progress in shaping a more modern civic minded society.